Digital technologies, employment and skills - Jelena Reljic; Rinaldo Evangelista; Mario Pianta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
The diffusion of digital technologies and their impact on employment and skills is investigated inthis article considering six major European countries (Germany, France, Spain, Italy, the Netherlands and the United Kingdom) and 42 manufacturing and service industriesover the 2009-2014 period. We analyse two key dimensions of digitalisation - industries' consumption of intermediate inputs from digital-intensive sectorsand investment in ICT tangible and intangible assets per employee. We first investigate their effect on total employment finding that job creation in industriesis supported by high digital consumption and reduced by high digital investment.We then explore how these variables have shaped the evolution of four professional groups - Managers, Clerks, Craft and Manual workers, defined on the basis of ISCO classes - and the increasingly polarisedskill structure of European economies.
Keywords: J23; J24; J21; O3; 330; Digital technology; Innovation; Employment; Skills; European industries